Developing Animal Picture Game to Improve Young English Learners’ Plural and Singular Mastery - Agus Hidayat; Septa Aryanika; Mohammad Ridho Kholid; Rohmatillah Rohmatillah; Nur Syamsiah; Nunun Indrasari; Dian Reftyawati (Jurnal Basicedu, 2022)
Interactive learning media can engage young learners to effectively absorb learning materials. Therefore, this developmental research was conducted to produce an interactive game that improves young learners' mastery of plural and singular nouns and enrich young learners' animal-related vocabulary. The researchers employed the ADDIE development model that began by analyzing problems related to the predetermined topic, analyzing the environment and work situation, designing the product, developing the product based on validation results from three expert validators, and conducting a product trial. The researchers investigated the product’s feasibility by performing a small-sccale trial and a large-scale trial. The research findings indicate that the developed interactive game was practical and useful. In short, the developed interactive game is feasible to assist young learners in learning plural and singular nouns and enrich their vocabulary.